Investigation and Characterization of Pathogens and Parasites on New Zealand Aquaculture Shellfish - Muznebin, Farhana (Auckland University of Technology, 2022)
Shellfish, including New Zealand Greenshell™ mussels (Perna canaliculus), New Zealand black-footed abalone (Haliotis iris) and flat oysters (Ostrea chilensis) are susceptible to a number of pathogens and diseases which threaten the aquaculture industry. In recent years, the high mortality of these species in both wild and farm settings has increased in frequency and magnitude. These mortality events often take place in summer (summer mortality), with shellfish succumbing to heat stress and pathogen loadings. However, there is a lack of information on the combined effects of acute heat stress and immune stimulation, as well as the specific mechanisms of the effects, susceptibility and resilience. Therefore, a better understanding is needed of the health status and capacity of shellfish to survive and overcome these events. Key to this understanding is the investigation of host-pathogen-environment interactions during mortality events and transmission pathways of infections. Histology, one of the most useful and imperative diagnostic techniques, was applied for the detection and identification of protozoa (Perkinsus olseni, apicomplexan X [APX], Bonamia exitiosa and B. ostreae, gut protozoan), ciliates (Scyphidia-like, Sphenophrya-like and unidentified disintegrated), fungi (Microsporidium rapuae), cestodes (Bucephalus longicornutus and Gymnophallid-like metacercaria), microbes (intracellular microcolonies of bacteria, Vibrio-like bacteria) and copepods from different tissues of H. iris, O. chilensis and P. canaliculus collected from Moana Blue Abalone Ltd., Kaiaua mussel farms and oyster farms in the Marlborough Sounds, New Zealand. Subsequent in situ-hybridization confirmed the identity of P. olseni in H. iris and P. canaliculus. This is the first detailed description of P. olseni in H. iris. There is a close relationship between the health status of abalone and the presence or absence of parasites, which may assist with identifying and characterising abalone health risks. Consequently, the findings of this thesis increase our in-depth understanding of pathogen infections in abalone, including host immune responses which may be used as early warning signs of health issues in wild and cultivated abalone in New Zealand. Furthermore, this is the first report on seasonal variations of P. olseni and APX in P. canaliculus. There was a significant association between seasons and the presence of P. olseni and APX in mussels. The abundance of B. ostreae, P. olseni and APX for whole animals and different tissues was evaluated semi-quantitatively using modified grading scales. Inflammatory tissue responses and abnormal tissue structures were also assessed semi-quantitatively. The modified grading schemes were employed to assess the health state of oysters, as well as improve the understanding of the progression of B. ostreae disease in oyster tissues. In this investigation, B. ostreae microcells were detected inside haemocytes of O. chilensis. The haemocytes presence in a variety of tissues within oysters indicated B. ostreae was present at these sites. Moreover, diapedesis was noticed in tissues containing B. ostreae in haemocytes and suggesting a route of disease transmission. A new classification scheme for P. canaliculus haemocytes was developed using Giemsa-stained smears, which is improved and more representative for the characterization of haemocytes (eight distinct types). The successful observation of phagocytic performance indicates that granulocytes only exhibit phagocytosis, and the phagocytic activity changed with season and temperature. Multidisciplinary methods including enzyme staining reactions, flow cytometry, and metabolomic profiling were used to investigate the combined effects of acute thermal stress and immune stimulation on mussels exposed to different temperatures (26°C vs 15°C) and endotoxin injection (with vs without). Positive enzyme reactions of the marker enzymes (acid phosphatase [ACP] and phenoloxidase [PO]) only detected in granulocytes, and for the first time, ACP and PO were evaluated in P. canaliculus. At the higher water temperature, free fatty acid constituents increased in mussel haemolymph and free amino acids decreased which supports higher energy demand and metabolic rate due to thermal stress. Survival data confirmed a severe physiological impact of the high-temperature treatment through incidences of mortality. However, thermal stress combined with endotoxin exposure did not lead to a synergistic effect on mortality. These findings provide new insights into the relationship between thermal stress and immunity to better understand the immune defence system in mussels. In summary, the information of this thesis helps to draw inferences about specific infection patterns relating to disease development and transmission mechanisms, assess host-pathogen interactions, to better understand the immune function and the overall health of shellfish for disease mitigation of these important aquaculture species. This information is crucial to develop disease management strategies and early warning systems for aquaculture species to ensure the sustainability of wild and farmed shellfish populations.